Kajian Strukturalisme dalam Puisi “Barangkali” Karya Amir Hamzah - RR. Nindya Aurellia Nugroho; Dwi Wahyu Candra Dewi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Literature and life complement each other, where literature serves as an expression of the soul that reflects beauty and cultural values. Poetry, one of the oldest forms of literature, holds meaning and imagination. This research focuses on the poem “Barangkali” by Amir Hamzah, who is famous for his ability to create an atmosphere of romanticism and spirituality. The purpose of the research is to analyze the inner and outer structure of the poem using a structuralism approach, so that readers can understand the relationship between form and meaning in poetry. The method applied is qualitative descriptive analysis, with the main data source of the poem. The results of the analysis show that the physical and inner structures of the poem collaborate to convey the worship of sublime love. Finding the theme, tone, atmosphere, and mandate in this poem underscores the spiritual depth and transcendental meaning contained therein. It is hoped that this research will be able to increase readers' understanding and appreciation of literary works, and encourage readers to be more critical and reflective in enjoying poetry. This analysis can then become a reference for further literary studies, especially related to classical poetry that is full of symbolic meaning.